Experimental Investigation on the Mechanical Properties of Cement Mortar Incorporated With Graphene and C&D Waste - Subedi, Asmita; Jha, Ankush; Deo, Pashupati; Dahal, Aagya (Journal of Advanced College of Engineering and Management, 2022)
Concrete is one among the essential materials utilized in engineering works.The two main properties which attribute to the reliability of concrete as a universal choice are strength and durability. Despite its remarkable properties, it has few shortcomings, namely, low tensile strength, low ductility, and unavoidable cracks. All of these inadequacies are the result of the relatively porous microstructure of concrete. The use of nanomaterials is the most influential and powerful alternative to overcome these limitations. In this paper, a comparative study of the mechanical properties of normal strength mortar over the mortar reinforced with graphene has been presented. Making use of the construction demolition waste in different proportions, namely, 25% and 50% as the partial replacement for fine aggregate, graphene was incorporated in the cement mortar of 1:3 grade in the proportion of 0.1%, 0.4%, 0.7%, and 1% by weight of cement respectively. The proportion of construction demolition waste and graphene were consequently varied and the corresponding change in mechanical properties, namely, compressive strength, tensile strength, and flexural strength of cement mortar was observed on the 7th day, 14th day, 21st day, and 28th day respectively and the same was compared with the result of normal mortar. It was observed that these mechanical properties increased with an increase in the proportion of graphene up to a certain limit after which it decreased. However, the optimum percentage of graphene varied along with the variation in the percentage of C&D waste.